Enhancing innovative thinking of digital technology teacher students by using project-based learning: Case of Nakhon Sawan Rajabhat University in Thailand - Buranahirun, Siribhorn; Philuek, Wudhijaya (Asian Journal of Contemporary Education, 2025)
This research aimed to study students’ innovative thinking by using Project-Based Learning. The quasi-experimental one-group pretest/posttest design was implemented for the target group, which consisted of 29 third-year Digital Technology teacher students who were enrolled in the second semester of the academic year 2023. Research instruments included learning management plans based on Project-Based Learning, an innovative thinking assessment form, and a project assessment form. The statistics such as percentage, mean, standard deviation, t-test, and Pearson's correlation coefficient were used for data analysis. The result showed 1) there was posttest score of all observed variables in innovative thinking higher than pretest, 2) there was different between pretest and posttest of latent variables in innovative thinking a significance level of 0.01 (p<.01), 3) the score of project works were between 77-88 points, 4) the correlation coefficients between observed variables with statistically significant values different from zero (p<.01) were 42 pairs and from zero (p<.05) were 21 pairs, and 5) the correlation coefficients between latent variables with statistically significant values different from zero (p<.01) were 6 pairs. The results show that Project-Based Learning can be used to promote innovative thinking in digital technology teacher-students, which may be applied to other teacher-students in the future.